PENGARUH PENGENDALIAN INTERN, KOMPETENSI SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA BAGIAN KEUANGAN (STUDI PADA SKPD KOTA DUMAI) - Vetty Rebecca Panjaitan; Nur Azlina; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence caused by internal control, the competence of human resources, organizational commitment and organizational culture on the financial section of the government performance in Dumai. This study used a purposive sampling with 99 people as samples . The technique of data collection on these studies is in the shape of a questionnaire, while the data analysis technique used multiple regression analysis were processed with SPSS program. The results of testing the hypothesis showed that the variables internal control, the competence of human resources and organizational commitment partially affect the variable government performance, while the partial organizational culture variable do not affect the variable government performance. The magnitude of the effect caused by Adjusted R square by four variables together against the dependent variable 32%, while the remaining 68% is affected by other variables not examined in this study.Keywords: internal control, human resources, commitment, culture, and performance